Pengaruh teknik relaksasi nafas dalam terhadap intensitas nyeri pada persalinan kala 1 fase laten - Safitri, Sila; Puspita, Richta; Sujiah, Sujiah (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Most mothers in labor will feel uncomfortable and disturbed by the pain experienced during the labor process. Excessive pain will affect the smoothness of the labor process. Purpose: To determine the effect of deep breathing relaxation techniques on the intensity of labor pain in the first stage of the latent phase. Methods: Quantitative research using Pre Experimental One Group Pretest- Posttest Design. Data collection from January to October 2024. The population of all maternal patients at the Wede Arrachman Pratama & Maternity Clinic in January-February. A sample of 37 people and analysis using univariate and bivariate using the T-test with a p value = (p <0.05). Results: The average labor pain in the first stage of the latent phase before the use of deep breathing relaxation techniques was 7.43 and the standard deviation was 0.647. The average labor pain in the first stage of the latent phase after the use of deep breathing relaxation techniques was 4.78 and the standard deviation was 1.084. In addition, the P-value was obtained as much as 0.000 (p<0.05). Conclusion: There is an influence of deep breathing relaxation techniques on reducing labor pain in the first stage of the latent phase.   Keywords: Deep Breath Relaxation Technique; Labor Pain; Latent Phase I Labor.   Pendahuluan: Sebagian besar ibu bersalin akan merasa tidak nyaman dan terganggu dengan rasa sakit yang dialami selama proses persalinan. Rasa sakit yang berlebihan akan berdampak pada kelancaran proses persalinan. Tujuan: Untuk mengetahui pengaruh teknik relaksasi nafas dalam terhadap intensitas nyeri persalinan kala 1 fase laten. Metode: Penelitian kuantitatif dengan menggunakan desain Pra Eksperimental One Group Pretest- Posttest Design. Pengumpulan data pada bulan Januari sampai Oktober 2024. Populasi seluruh pasien ibu bersalin di Klinik Pratama & Bersalin Wede Arrachman pada Bulan Januari-Februari. Sampel sebanyak 37 orang dan analisis menggunakan univariat dan bivariate menggunakan uji T-test  dengan nilai p = (p<0,05). Hasil: Rata-rata nyeri persalinan kala 1 fase laten sebelum penggunaan teknik relaksasi nafas dalam 7.43 dan standard deviation sebesar 0.647. Rata-rata nyeri persalinan kala 1 fase laten sesudah penggunaan teknik relaksasi nafas dalam 4.78 dan standard deviation sebesar 1.084. Selain itu, perolehan Nilai P-value sebesar 0.000 (p<0.05). Simpulan: Ada pengaruh teknik relaksasi nafas dalam terhadap penurunan nyeri persalinan kala 1 fase laten   Kata Kunci: Nyeri Persalinan; Persalinan Kala I Fase Laten; Teknik Relaksasi Nafas Dalam.